Cytogenetic and molecular evidence for two species in the Anopheles barbirostris complex (Diptera: Culicidae) in Thailand - Saeung A. (2014)
Seventeen isolines of Anopheles barbirostris derived from animal-biting female mosquitoes showed three karyotypic forms: Form A (X2, Y 1) in five isolines from Phetchaburi province; Form B (X1, X3, Y2) in three and eight isolines from Chiang Mai and Ubon Ratchathani provinces, respectively; Form C (X2, Y3) in one isoline from Phetchaburi province. All 17 isolines exhibited an average branch summation of seta 2-VI pupal skins ranging from 12.1-13.0 branches, which was in the limit of A. barbirostris (6-18 branches). Of the 12 human-biting isolines from Chiang Mai province, five isolines showed Form B (X2, Y2), and seven isolines exhibited a new karyotypic form designated as Form E (X2, Y5). All of 12 isolines had an average branch summation of seta 2-VI pupal skins ranging from 22.4-24.5 branches, which was in the limit of Anopheles campestris (17-58 branches). Thus, they were tentatively designated as A. campestris-like Forms B and E. Hybridization between A. campestris-like Forms B and E showed that they were genetically compatible, yielding viable progeny for several generations suggesting conspecific relationships of these two karyotypic forms. Reproductive isolation among crosses between A. campestris-like Form B and A. barbirostris Forms A, B, and C strongly suggested the existence of these two species. In addition, the very low intraspecific variation (genetic distance <0.005) of the nucleotide sequence of ITS2 of the rDNA and COI and COII of mitochondrial DNA of the seven isolines of A. campestris-like Forms B and E supported their conspecific relationship. The large sequence divergence of ITS2 (0.203-0.268), COI (0.026-0.032), and COII (0.030-0.038) from genomic DNA of A. campestris-like Forms B and E and the A. barbirostris Forms A, B, and C clearly supported cytogenetic and morphological evidence. © 2007 Springer-Verlag.